2013
DOI: 10.1371/journal.pone.0053981
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Alternative Splicing Mutation in AIRE Gene Causes Autoimmune Polyendocrine Syndrome Type 1

Abstract: Autoimmune polyendocrine syndrome type 1 (APS-1) is a rare autosomal recessive disease defined by the presence of two of the three conditions: mucocutaneous candidiasis, hypoparathyroidism, and Addison’s disease. Loss-of-function mutations of the autoimmune regulator (AIRE) gene have been linked to APS-1. Here we report mutational analysis and functional characterization of an AIRE mutation in a consanguineous Chinese family with APS-1. All exons of the AIRE gene and adjacent exon-intron sequences were amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Another SNP, ss107794716 residing within the AIRE gene, was identified by both of RD and Cohen’s h but not OR (RD = 0.006, p = 0.034; Cohen’s h = 0.106, p = 0.019; OR = 7.04, p = 0.068). The association of this region and the AIRE gene with T1D was documented [ 35 37 ]. In addition, the magnitudes of p-values of significant rare variants obtained from Cohen’s h are the smallest.…”
Section: Resultsmentioning
confidence: 99%
“…Another SNP, ss107794716 residing within the AIRE gene, was identified by both of RD and Cohen’s h but not OR (RD = 0.006, p = 0.034; Cohen’s h = 0.106, p = 0.019; OR = 7.04, p = 0.068). The association of this region and the AIRE gene with T1D was documented [ 35 37 ]. In addition, the magnitudes of p-values of significant rare variants obtained from Cohen’s h are the smallest.…”
Section: Resultsmentioning
confidence: 99%
“…Primers are summarized in Table S2. A modified pcDNA3 minigene was used as the empty native minigene (vector), and was linearized by using Xba I and Xho I (Takara, Dalian, China). The wild‐type (WT) and mutant minigene were constructed by ligating the PCR products into linearized vector (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Minigene splicing assay is more frequently used . Cloning three consecutive exons, the affected exon and two flanking exons, into the minigene system may better mimic the procedure of pre‐RNA splicing in vivo , because it can retain the original ss sequences of upstream and downstream introns of the affected exon . The effects on pre‐RNA splicing can also be predicted by in silico tools, including MaxEntScan (MES), Splice‐Site Prediction by Neural Network (NNSplice), Human Splicing Finder (HSF), Splice‐Port, Exonic Splicing Enhancers (ESE) Finder, and RESCUE‐ESE, but they are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…11 To date, more than 100 APS-1 causing mutations have been identified which vary from substitutions, insertions and deletions to splice-site mutations. [12][13][14] Several studies have demonstrated that AIRE/ Aire is expressed mainly by the thymus, in a subpopulation of medullary thymic epithelial cells (mTECs), AIRE + mTECs. 9,[15][16][17] AIRE/Aire promotes self-tolerance in the thymus by regulating the promiscuous expression of a wide array of tissuespecific antigens (TSAs).…”
Section: Introductionmentioning
confidence: 99%